Projecting the African society and cultural values: Chinua Achebe’s Things Fall Apart (1958) - Essuman, Jonathan (Research Journal in Advanced Humanities, 2021)
Since literature is acknowledged as a reflector of the modern or contemporary society, it is therefore not out of place to claim that a writer’s experiences, community or society influences his or her work. Individual writers have pertinent themes that drive their focus in their creative works and these themes more often align with the society. Hence, to separate the society from literature is to take life from an individual. Achebe’s quest to present the theme of social disintegration and misplaced cultural identity undoubtedly presents the setting of the Nigerian community to his readers. This paper aimed at investigating the techniques that Achebe employs and critically reviewing his presentation of the African society and cultural values in his creative work; Things Fall Apart. Again, it analyzed and appreciated the relevance, the creativity and inventiveness of African writers in writing on the various subject matters and themes that reside in the African society and depict the African values or culture. The findings revealed that Achebe successfully uses diction, figurative language, proverbs, characterization and narrative technique to project the African society and cultural values.